Attitudes About Informed Consent: An Exploratory Qualitative Analysis of UK Psychotherapy Trainees - Blease, Charlotte R.; Arnott, Tim; Kelley, John M.; Proctor, Gillian; Kube, Tobias; Gaab, Jens; Locher, Cosima (Frontiers in Psychiatry, 2020)
Background: Ethical informed consent to psychotherapy has recently been the subject of in-depth analysis among healthcare ethicists. Objective: This study aimed to explore counselling and psychotherapy students’ views and understanding about informed consent to psychological treatments. Methods: Two focus groups were conducted with a total of ten students enrolled in a Masters course in counselling and psychotherapy at a British university. Questions concerned participants’ understanding of informed consent including judgments about client capacity; the kinds of information that should be disclosed; how consent might be obtained; and their experiences of informed consent, both as a client and as a therapist. Focus groups were audio-recorded, transcribed, and analyzed using qualitative content analysis. Coding was conducted independently by three authors. Results: Comments were classified into three main themes: (1) the reasons and justifications for informed consent; (2) informed consent processes; and (3) the hidden ethics curriculum. Some trainees expressed significant doubts about the importance of informed consent. However, participants also identified the need to establish the clients’ voluntariness and their right to be informed about confidentiality issues. In general, the format and processes pertaining to informed consent raised considerable questions and uncertainties. Participants were unsure about rules surrounding client capacity; expressed misgivings about describing treatment techniques; and strikingly, most trainees were skeptical about the clinical relevance of the evidence-base in psychotherapy. Finally, trainees’ experiences as clients within obligatory psychotherapy sessions were suggestive of a ‘hidden ethics curriculum’ – referring to the unintended transmission of norms and practices within training that undermine the explicit guidance expressed in formal professional ethics codes. Some students felt coerced into therapy, and some reported not undergoing informed consent processes. Reflecting on work placements, trainees expressed mixed views, with some unclear about who was responsible for informed consent. Conclusions: This qualitative study presents timely information on psychotherapy students’ views about informed consent to psychotherapy. Major gaps in students’ ethical, conceptual, and procedural knowledge were identified, and comments suggested the influence of a hidden curriculum in shaping norms of practice. Implications: This exploratory study raises important questions about the preparedness of psychotherapy students to fulfil their ethical obligations.